2007
DOI: 10.1093/hmg/ddm028
|View full text |Cite
|
Sign up to set email alerts
|

COG8 deficiency causes new congenital disorder of glycosylation type IIh

Abstract: We describe a new Type II congenital disorder of glycosylation (CDG-II) caused by mutations in the conserved oligomeric Golgi (COG) complex gene, COG8. The patient has severe psychomotor retardation, seizures, failure to thrive and intolerance to wheat and dairy products. Analysis of serum transferrin and total serum N-glycans showed normal addition of one sialic acid, but severe deficiency in subsequent sialylation of mostly normal N-glycans. Patient fibroblasts were deficient in sialylation of both N- and O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 37 publications
7
120
0
2
Order By: Relevance
“…Mutations in the genes encoding human COG1, COG4-COG8 have been associated with congenital disorders of glycosylation (CDG) (Foulquier et al, 2006;Foulquier et al, 2007;Kranz et al, 2007;Lübbehusen et al, 2010;Ng et al, 2007;Paesold-Burda et al, 2009;Reynders et al, 2009;Spaapen et al, 2005;Steet and Kornfeld, 2006;Wu et al, 2004) suggesting a role for COG in the retention and/or retrieval of Golgi glycosylation enzymes. Indeed, loss of COG subunits impaired the localisation and the stability of Golgi resident proteins, which are known to recycle within the Golgi stacks (Oka et al, 2004;Zolov and Lupashin, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the genes encoding human COG1, COG4-COG8 have been associated with congenital disorders of glycosylation (CDG) (Foulquier et al, 2006;Foulquier et al, 2007;Kranz et al, 2007;Lübbehusen et al, 2010;Ng et al, 2007;Paesold-Burda et al, 2009;Reynders et al, 2009;Spaapen et al, 2005;Steet and Kornfeld, 2006;Wu et al, 2004) suggesting a role for COG in the retention and/or retrieval of Golgi glycosylation enzymes. Indeed, loss of COG subunits impaired the localisation and the stability of Golgi resident proteins, which are known to recycle within the Golgi stacks (Oka et al, 2004;Zolov and Lupashin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, subunits of Lobe A are essential components of the complex (VanRheenen et al, 1998;Whyte and Munro, 2001;Wuestehube et al, 1996), whereas Lobe B subunits are not substantially required for cell growth or internal membrane organisation (Ram et al, 2002;Whyte and Munro, 2001). Mutations in the genes encoding human COG1, COG4-COG8 have been associated with congenital disorders of glycosylation (CDG) (Foulquier et al, 2006Foulquier et al, 2007Kranz et al, 2007;Lübbehusen et al, 2010;Ng et al, 2007;Paesold-Burda et al, 2009;Reynders et al, 2009;Spaapen et al, 2005;Steet and Kornfeld, 2006;Wu et al, 2004) indicating a role for COG in the transport and/or stability of Golgi glycosylation enzymes. Indeed studies in both yeast and mammalian cells have suggested that COG complex might function as a vesicle-tethering factor in intra-Golgi retrograde COPI transport (Ungar et al, 2002), thus regulating the distribution and the stability of Golgi resident proteins (Oka et al, 2004;Shestakova et al, 2006;Suvorova et al, 2001;Suvorova et al, 2002;Walter et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Among the known multisubunit tethering complexes, only COG (23)(24)(25)(26)(27)(28) and TRAPP (29) have been directly implicated in human genetic disease. Mutations in the Cog1 (24), Cog7 (26)(27)(28), and Cog8 (23,25) subunits cause type II congenital disorders of glycosylation (CDGs).…”
mentioning
confidence: 99%
“…Mutations in the Cog1 (24), Cog7 (26)(27)(28), and Cog8 (23,25) subunits cause type II congenital disorders of glycosylation (CDGs). Type II CDGs lead to a wide variety of neurological and developmental abnormalities brought on by defects in the processing of N-linked glycan chains [for review, see (30)].…”
mentioning
confidence: 99%
“…The most severe diseases are observed for COG6, COG7 and COG8 mutations, associated with severe neurological impairment, liver dysfunction, and infantile lethality [52][53][54][55]. The identification of milder cases of COG6 and COG7 deficiency harboring different mutations [56,57] however shows that the severity of the disease does not simply relate to the subunit affected but rather to the capability of forming a fully functional COG complex.…”
Section: Localization Of Glycosyltransferasesmentioning
confidence: 99%